Enhancing Da’wah and Spread of Knowledge Via Social Media Platforms - Sule, Muhammad Maga; Sulaiman, Yahaya (SCAD Independent, 2021)
This research centered on enhancing Islamic Da’wah and Islamic teachings through the usage of social media. The purpose of this research was to examine how Muslims make use of social media to enhance Da’wah and Islamic knowledge among Muslims and non-Muslims, and the various Muslim scholars and groups on social media platforms who utilized the new technology to propagate the message of Islam. The paper adopted qualitative and analytical research methodologies in analyzing the issue in the research article, the paper also conducted an in-depth interview with two respondents at different intervals. Consequently, this paper explored the newest means of tapping the treasures of social media towards augmenting Da’wah activities and spreading the knowledge of Islam. The paper identified various individual Muslim scholars and groups that created pages/channels on Facebook, YouTube, WhatsApp, Telegram, Twitter, and other social media platforms to enhance Islamic da’wah and knowledge. Hence, the paper found out that social media is a workable and genuine tool for the propagation ideals of Islam.